Chapter 6: Unlocking big data: at the crossroads of computer science and the social sciences - Posegga, Oliver (Edward Elgar Publishing, 2023)
Digital data on human behaviour and social interactions are a seemingly abundant and valuable resource of the twenty-first century, promising deep insights into the social processes generating them. Such data - commonly referred to as digital trace data, process-generated data, or digital behavioural data - are increasingly available to us, but the goal of unlocking their potential remains elusive despite the emergence of specialized fields such as computational social science, which has produced an ample body of research based on this resource. Achieving that goal requires revisiting the foundations of research based on this data type, a thorough understanding of its unique characteristics, overcoming access barriers, understanding data generating processes, and rethinking the role of theory at the intersection between computer science and social science. This chapter discusses the origin and characteristics of such data, as well as the interdisciplinary challenges researchers face in accessing, understanding, and using it for research.